PERAN ORANG TUA DALAM MEMBANGUN KONSENTRASI BELAJAR SISWA (STUDI KASUS SDN RENGASPENDAWA 04) - Maulidah, Izza; Didik Tri Setiyoko; Atikah Mumpuni (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research is motivated by the low concentration of elementary school students' learning, characterized by a lack of focus and easy distraction. This study aims to analyze the role of parents in building student learning concentration and identify factors that influence it at SDN Rengaspendawa 04. This study uses a qualitative approach with a case study type. The research subjects include parents and students. Data collection techniques are carried out through interviews, observation, and documentation, while data analysis uses an interactive model with triangulation to test the validity of the data. The results show that the role of parents as motivators, guides, supervisors, and educators can improve students' focus, discipline, and learning resilience. Learning concentration is also influenced by internal and external factors, including physical conditions and the learning environment.